A narrative review of the role of gastrointestinal dysbiosis in the pathogenesis of polycystic ovary syndrome - Jim Parker; Claire O'Brien; Jason Hawrelak (Korean Society of Obstetrics and Gynecology, 2022)
Diet-induced gastrointestinal dysbiosis has been hypothesized to play a significant role in stimulating an increase in gastrointestinal permeability and activating systemic inflammation in women with polycystic ovary syndrome (PCOS). We reviewed the current proof-of-concept studies on the proposed mechanism of dysbiosis in the pathogenesis of PCOS. A literature search was performed to identify articles on changes in the intestinal microbiome (dysbiosis) and increased intestinal mucosal permeability involving lipopolysaccharide (LPS), LPS-binding protein (LPS-BP), and zonulin. We also searched for systematic reviews and meta-analyses that synthesized the results of studies on the therapeutic effects of prebiotics, probiotics, or synbiotics in women with PCOS. Our search was confined to human studies between 2012 and 2021 using the PubMed, Scopus, and Cochrane databases. Thirty-one studies met the inclusion criteria (14 microbiota, 1 LPS, 1 LPS-BP, 1 LPS and LPS-BP, 5 zonulin, 9 systematic reviews). Our analysis revealed that most studies reported reduced alpha diversity and dysbiosis in women with PCOS. Preliminary studies suggest that LPS, LPS-BP, and zonulin may be involved in the pathophysiology of increased intestinal permeability. Treatment of PCOS with prebiotics, probiotics, and synbiotics appears to have a range of beneficial effects on metabolic and biochemical profiles. This review highlights the need for continued research into the pathophysiological mechanisms of dysbiosis and the clinical efficacy of prebiotics, probiotics, and synbiotics in women with PCOS.